Statistical data cleaning with applications in R - Loo, Mark van der; Jonge, Edwin de (John Wiley & Sons, Inc., 2018)
The production of clean data is a complex and time-consuming process that requires both technical know-how and statistical expertise. This book examines technical data cleaning methods relating to data representation and data structure. A prominent role is given to statistical data validation, data cleaning based on predefined restrictions, and data cleaning strategy.